Implementasi Model Pembelajaran Make a Match pada Pembelajaran Sejarah Kebudayaan Islam Kelas XI di MAN 4 Agam Kec. Tanjung Raya - Chaniago, Linia Chindi; Ilmi, Darul; Zakir, Supratman; Jasmienti, Jasmienti (ARZUSIN, 2023)
This research is motivated by the implementation of the make a match learning model which has not been running properly. The make a match model (looking for pairs of cards) requires media in the form of cards containing questions and answers. Question and answer card material that should have been made by the teacher was in fact made by the students. This causes some students to be less precise in making questions. They also asked each other about the questions and answers they made, so they already knew the questions and answers beforehand. Determination of time and student confidence are also needed so that students do not carelessly match cards without being guided by the topic of the material being studied. The purpose of this study was to determine the implementation of the make a match model in class XI SKI learning at MAN 4 Agam Kec. Tanjung Raya. The type of research used is field research (field research). This research is descriptive qualitative which aims to describe the research results in accordance with the actual data. The informants in this study were divided into two, namely key informants and supporting informants. The key informants were class XI SKI teachers, while the supporting informants were class XI MIPA 2 students and Waka. Curriculum MAN 4 Religion. Data collection techniques using observation, interviews, and documentation. The results of the research can be stated that the implementation or implementation of the make a match model used by the teacher in the material "Reform Movement in Islam" has been carried out properly and correctly. This can be seen from the steps of the make a match model carried out by the teacher in SKI learning in the right class.